Penerapan Arsitektur Islam pada Pusat Perbelanjaan Produk Islami di Kota Gorontalo - Nofanti Maabu; Sri Sutarni Arifin; Moh. Faisal Dunggio (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Gorontalo is a province in Indonesia experiencing continuous economic growth, as evidenced by data from the Statistics (BPS) of Gorontalo Province, which shows that the contribution of the Gross Regional Domestic Product (GRDP) by sector in the fourth quarter of 2023 indicates a 13.78% share from the trade sector. Gorontalo City has seen commercial businesses grow, such as shophouses, minimarkets, supermarkets, and various stalls selling Islamic products throughout the city. The dispersed nature of Islamic product sales creates a challenge for the Muslim community in quickly finding the products and services they need. Therefore, an Islamic product shopping center is proposed as a space facilitating interaction between sellers and buyers of Islamic products. The objective of designing an Islamic product shopping center is to create a commercial facility with Islamic architectural characteristics, situated on a site that supports the activities required to serve as a hub for production, promotion, consultation, and sales. The study method employed is a descriptive approach involving collecting and analyzing primary and secondary data. The analysis identifies the potential, issues, and solutions related to the design of the Islamic product shopping center. This design is expected to serve as a central shopping venue that accommodates the activities of both traders and consumers of Islamic products.